Baseline characteristics predict risk of progression and response to combined medical therapy for benign prostatic hyperplasia (BPH). (13th August 2014) - Kozminski, Michael A.; Wei, John T.; Nelson, Jason; Kent, David M.
<x xml:space="preserve">Abstract</x> Objective To better risk stratify patients, using baseline characteristics, to help optimise decision‐making for men with moderate‐to‐severe lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPH) through a secondary analysis of the Medical Therapy of Prostatic Symptoms (MTOPS) trial. Patients and Methods After review of the literature, we identified potential baseline risk factors for BPH progression. Using bivariate tests in a secondary analysis of MTOPS data, we determined which variables retained prognostic significance. We then used these factors in Cox proportional hazard modelling to: i) more comprehensively risk stratify the study population based on pre‐treatment parameters and ii) to determine which risk strata stood to benefit most from medical intervention. Results In all, 3047 men were followed in MTOPS for a mean of 4.5 years. We found varying risks of progression across quartiles. Baseline BPH Impact Index score, post‐void residual urine volume, serum prostate‐specific antigen (PSA) level, age, American Urological Association Symptom Index score, and maximum urinary flow rate were found to significantly correlate with overall BPH progression in multivariable analysis. Conclusions Using baseline factors permits estimation of individual patient risk for clinical progression and the benefits of medical therapy. A novel clinical decision tool based on these analyses will allow clinicians to weigh patient‐specific benefits against possible risks of adverse effects for a given patient.